Winner take all : China's race for resources and what it means for the world - Moyo, Dambisa (New York : Basic Books, 2012)
Discusses the commodity dynamics that the world will face over the next several decades and, in particular, the implications of China's rush for resources across all regions of the world.
Includes bibliographical references (p. 239-245) and index.
Keywords: Industrialization -- China; Commodity control; Commodity exchanges; Power resources -- Economic aspects; Natural resources; Investments, Foreign -- China; China -- Foreign economic relations; China -- Economic policy -- 2000-